Pengaruh Kompentensi SDM dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan PT. Pelindo Regional I - Malkit Kaur; Selvi Aristantya; Irna Triannur Lubis (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This research aims to determine and analyze the influence of human resource (HR) competence and the use of information technology on the quality of financial reports at PT. Pelindo Regional 1. The research method used is multiple regression analysis, which makes it possible to test the relationship simultaneously between several independent variables and the dependent variable. In this case, the independent variables studied are HR competency and use of information technology, while the dependent variable is the quality of financial reports. The population in this study consisted of 30 employees at PT. Pelindo Regional 1, and by using a saturated sample, all of them were used as samples, so that 30 respondents were obtained. The type of data used in this research is primary data, which was obtained through distributing questionnaires to employees selected as respondents. The collected data was then analyzed using multiple regression statistical tools to test the influence of independent variables on the quality of financial reports. The results of this research show that human resource competency has a significant influence on the quality of financial reports at PT. Pelindo Regional 1. This shows that the higher the competency possessed by employees, especially in terms of knowledge and skills in accounting and finance, the better the quality of the financial reports produced.